New York : a chronological & documentary history, 1524-1970 - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1974)
Includes a chronology of events in St. Louis' history and a selection of pertinent documents.
Bibliography: p. 139-149.
Keywords: Saint Louis (Mo.) -- History -- Chronology; Saint Louis (Mo.) -- History -- Sources; Saint Louis (Mo.) -- History